THE UTILIZATION OF DIGITAL TECHNOLOGY FOR MSME AND TOURISM PERFORMERS DURING PANDEMIC IN MENDALA VILLAGE SIRAMPOG BREBES - M. Farrij Karbana; Fatiatun Fatiatun (Universitas Airlangga, 2022)
Economic development during the pandemic is very slow. This article aims to find out various economic sectors that can be further developed through advances in digital technology during the pandemic in Mendala village, Kec. Sirampog. In Mendala village there are many micro, small, and medium enterprises (MSMEs) that have the characteristics of the products they produce. This is an opportunity for them to develop their business. Advances in technology can help them to be more advanced, but due to limited knowledge, their development has not been seen. In addition to MSME participants, the sector that is most affected by the pandemic is the tourism sector. In Mendala village several tourism places have potential. One way is by utilizing digital technology, such as social media and others. During the pandemic, the number of visitors to each tourism place is greatly reduced. Therefore, by using digital technology, it is hoped that it can attract visitors and can help people in the economic sector.